Student's Behavioral Engagement on The Use Of Wordwall.Net In Vocabulary Learning - Khoirunnisa, A'qilah; Miftak, Fauzi; Fitriyana, Wahyudin (Peneliti.net, 2023)
This research aims to see how students engage behaviorally in using Wordwall.Net in vocabulary learning at vocational high schools. This research used a qualitative approach and case study method. The research data was collected from observations in the classroom during students' use Wordwall.Net as learning media and verified by interview data after using Wordwall.Net in vocabulary learning. This research was conducted at a Vocational high school in East Jakarta. One class was observed for two meetings during vocabulary learning mediated Wordwall.Net, and six students were interviewed to find out their perspective towards the web tool Wordwall.Net. The interview data of this research was gained with ten questions for interview guidelines. The data from observations and interviews were analyzed using A six-phase method by Braun & Clarke (2006) and interpreted. This research found that using Wordwall.Net in vocabulary learning at vocational high school positively impacts students' engagement in behavioral aspects. Students pay attention marked by responses during the vocabulary learning, students' study habits from two meetings improve each day, and students respond to rules and instructions during the learning process marked by the students finish all task and submit it on time.